Study of the transtextuality in the cinema of Quentin Tarantino (2021)
Cinema and literature have broad and important practical and theoretical relationships. In relation to the latter, the theory of transtextuality, created by Gérard Genette, has played a fundamental role, due to the vast number of references that have been made to audiovisual or literary works in other films.By virtue of the former, we apply Genette’s types of transtextualities along with the cinematographic notions created by Robert Stam and other theorists based on his postulates to analyze and exemplify some of the most notorious transtextual relationships in Quentin Tarantino’s filmography, currently notorious filmmaker in this field. Therefore, we find that there is a large and special amount of transtextual connections in his films,which is important to demonstrate the relevance of this in his authorship and in the aforementioned relationship between literature and cinema.